Adherence and barriers to contraceptive use in young adult women attending first level health care facilities, Peru - Gutierrez Crespo, Hugo; Huamán Carhuas, Luis; Cehua Alvarez, Efrain Antonio; Matzumura Kasano, Juan Pedro; Valdiglesias Ochoa, Diana (Medicina Clínica y Social, 2023)
Introduction: In developing countries, the existence of barriers to women's access to contraception generates low adherence to the use of different contraceptive methods. Objective: To describe the adherence and barriers in the use of contraceptive methods in a population of adult women. Methodology: Quantitative, observational, descriptive, cross-sectional study, with a non-probabilistic sample of women over 18 years of age attended at a first level health center, to whom selection criteria were applied and voluntary consent was obtained for their participation. The study followed the Helsinki principles and was approved by the Ethics Committee of the Peruvian Society of Obstetrics and Gynecology. The instrument used was the IRB Study (Barriers to adolescent contraception adherence) with a Cronbach Alpha consistency of 0.79. Descriptive statistics and Fisher's exact test were used for bivariate analysis. Results: A total of 353 women participated, the mean age was 24.6 ± 4.2 years; 65.7% were single and 19.5% were cohabiting; 58.4% reported university education; 73.7% were Catholic compared to 26.3% Evangelical. Male condoms (37.2%) and oral pills (23%) were the most commonly used methods. Fear of the side effects of contraceptives (66.2%) and travel to the health center for control (23.5%) were the main obstacles. Discussion: Age and sexual activity were factors associated with contraceptive adherence. Concern about weight gain, bleeding and health risk were the main barriers.
Keywords: acces; contraception; women